PENGARUH MEDIA PEMBELAJARAN INTERAKTIF TERHADAP MINAT DAN KEMAMPUAN PEMAHAMAN KONSEP SISTEM EKSKRESI SISWA MTS SWASTA DARUL MUTTAQIN KANDANGAN - Pratiwi, Dian; Hulu, Irwan Lihardo; Huda, Muhammad Komarul (Jurnal Metabio, 2024)
This study aims to determine the effect of interactive learning media on the interest and ability to understand the concept of the excretory system of students at MTs Swasta Darul Muttaqin Kandangan in the 2021/2022 Academic Year. The population in this study was all class VIII consisting of 2 classes with a total of 64 students. Sampling was carried out using nonprobability sampling, namely the entire population is a sample. Data analysis was carried out by determining the validity test, reliability test, normality test, homogeneity test and hypothesis test, proven by the "t test" at a significance level of α = 0.05. From the results of the study, the overall results of respondents' answers about students' interest in learning using interactive media showed that the statement results were always 54.7%, statements often 39.2% and the rest of the students chose other statement options 6%. The results of the study showed that the average posttest value of the experimental class was 88.75. While the average posttest value of the control class was 86.25. From the results of the hypothesis testing, it was obtained that t_count (1.79)> t_table (1.66) at a significance level of α = 0.05 with df = 63. So H0 is rejected, Ha is accepted, meaning that there is an influence of media and students' conceptual understanding of the excretion system material in class IX MTs Darul Mutaqin Kandangan in the 2021/2022 academic year. The overall results of respondents' answers regarding interactive learning media showed that the results of the statement were very good at 50.07%, the statement was good at 43.4% and the rest of the students chose other statement options at 6.48%.